Family CPR and first aid for choking - Blackboard Productions (Canada : Blackboard Productions, 1999)
Tjis instructional video is a complete guide on CPR and basic life saving techniques that can be applied to adults, children and infants.
Keywords: Cardiopulmonary resuscitation; First aid